Reliability of rehabilitative ultrasound imaging for the medial gastrocnemius muscle in poststroke patients. (12th June 2013) - Cho, Ki Hun; Lee, Hwang Jae; Lee, Wan Hee
Summary Objective The purpose of this study was to evaluate the suitability of rehabilitative ultrasound imaging for quantification of medial gastrocnemius muscle in poststroke patients. Participants Thirty stroke patients (15 men and 15 women; age 64·7 ± 5·66 years; stroke duration 437·40 ± 168·24 days) participated in this study. Methods Real‐time B‐mode ultrasonography with a 7·5‐MHz linear transducer was used to measure pennation angle and muscle thickness of the medial gastrocnemius muscles with ankle joint 90° and maximal plantar flexion. Two examiners acquired images from all participants during three separate testing sessions. After the first measurement was performed, the second measurement was performed one hour later, and the third measurement was performed 1 week later. Intraclass correlation coefficients (ICCs(3, 1)) were used for estimation of reliability. Results The ICC (95% CI) for all intra‐examiner reliability was good to very good, ranging from 0·69 to 0·99 (0·51–0·99), and the ICC for all interexaminer reliability was good to very good, ranging from 0·70 to 0·99 (0·46–0·99). Conclusion In this study, the intra‐ and interexaminer reliability of the pennation angle and muscle thickness measurements of the medial gastrocnemius muscle was good to very good. Therefore, we suggest that the pennation angle and muscle thickness measurements of the medial gastrocnemius muscle obtained from rehabilitative ultrasound imaging would be useful for clinical assessment in poststroke patients.